NanoRound: A benchmark study on the numerical approach in nanofluids' simulation. (November 2019) - Minea, Alina Adriana; Buonomo, Bernardo; Burggraf, Jonas; Ercole, Davide; Karpaiya, Kavien Raaj; Di Pasqua, Anna; Sekrani, Ghofrane; Steffens, Jan; Tibaut, Jan; Wichmann, Niklas; Farber, Peter; Huminic, Angel; et al.
Abstract: Numerical simulation of nanofluid flows is of maximum importance for a large area of applications, especially in the solar energy technology. Even though a lot of numerical studies are available in the open literature, there is still a large debate in regard to the most appropriate approach when dealing with nanofluids. Plus, a precise simulation of the thermal fluid-solid system encompasses a profound understanding of the fundamental physical phenomena that appear in the nanofluid flow. In this idea, a number of simplifications and approaches are considered, and the aim of this benchmark study is to shed some light in the most suitable CFD approach when dealing with nanofluid flow. Finally, different approaches were considered by different research groups with relevant experience in CFD and are discussed accordingly and in connection with an experimental case that was chosen as a comparison. The current benchmark study was projected to be an ample reference for investigators interested in dealing with the numerical study of the nanofluids' flow. Highlights: A benchmark study was performed on nanofluids' simulation. A comparison was performed with experimental data Single- and multi-phase models were compared. It was shown that gravity has an influence on the nanofluid flow.